Lymph node retrieval is inferior in the modified Merendino resection for early Barrett’s carcinoma: a matched-pair comparison with Ivor Lewis resection - Haist, Thomas; Lorenz, Dietmar (World journal of surgery, 2017)
Aim of the studyA matched-pair comparison between the modified Merendino resection (MER) and Ivor Lewis resection (ILR) for early Barrett’s carcinoma.BackgroundEarly adenocarcinoma of the esophagus (eACE) with positive risk factors for lymph node metastasis (LNM) needs surgery for cure. MER appeared to be an alternative to ILR.MethodsBetween July 2000 and July 2012, 156 patients with high-grade dysplasia or eACE received ILR, whereas in 30 cases MER was performed in a tertiary care center for GI Surgery. A matched-pair analysis was performed on the basis of sex, age, BMI, ASA classification and tumor stage. Thirty patients were assigned to each group. The data were analyzed regarding perioperative aspects (e.g., operating time, hospital stay, complications, number of lymph nodes) and survival analysis.ResultsThe mean operating time was 301.7 min for ILR, compared to 255.4 min for MER (p = 0.044). The hospital stay following ILR was significantly longer than for MER (22.4 days ILR vs. 16.4 days MER, p = 0.023). There was no statistically significant difference regarding complications between the two groups (p = 0.463). The number of resected lymph nodes was significantly lower in the MER group (median 21) compared to the ILR group, where a median of 31 lymph nodes could be removed (p < 0.001). There was no statistically significant difference in overall (p = 0.145) or tumor-specific survival (p = 0.353).ConclusionsLymph node retrieval is significantly inferior in the MER. Postoperative complication rates were comparable between the two operating techniques, although the operation time for ILR took longer and these patients required a longer hospital stay. MER should not be applied in cases with high risk of LNM.
Gesehen am 07.11.2018